A CASE AMONG FINAL YEAR STUDENTS IN SCHOOL OF TECHNOLOGY MANAGEMENT AND LOGISTIC (STML) UNIVERSITI UTARA MALAYSIA : THE EFFECT OF COVID-19 ON EDUCATION - Nahdatul Haziqah Abdul Malik; Lim Kong Teong, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The worldwide economic slump and its considerable impact on the higher education sector have been attributed to the COVID-19 pandemic. Campuses were closed suddenly as a social distancing tactic to avoid community transmission; therefore, in-person classes have transitioned to online learning. Because of this, there has been a change in attention to the use of online learning tools and platforms for effective student participation, which may be too expensive or unavailable for some students. Understanding how online education can affect a student's emotional well-being and social life is crucial. Consequently, the purpose of this research is to explore how the effects of COVID-19 on students' mental health and social life are connected to their schooling. The studies focus on three areas that could affect students' emotional and social well-being: classroom procedures, counselling, and evaluation strategies. These students' emotional and social well-being is the primary focus of this investigation, and the researchers hope to identify not only the elements that have the most bearing on these outcomes but also the relationships between independent and non-independent variables. One hundred fifty undergraduates in their last year from the School of Technology Management & Logistics (STML) at the Universiti Utara Malaysia (UUM) filled out a questionnaire to provide us with this information. The analysis was performed using SPSS, a statistical package. It appears from the results that instructional approaches, guidance, and assessment methods all have an effect on the dependent variable (mental health as well as the social life of students).